Pengembangan Video Program Event Smart Shopper Surprize Sebagai Media Promosi Tangcity Mall - Anita B. Wandanaya; Dewi Immaniar Desrianti; Piyan Sopyan (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2021)
Organizing a program & event is one of the efforts made by a Mall in maintaining its existence in the community. The same is done by Tangcity Mall, an exclusive Golden Icon shopping center in the Tangerang City area. The event program being held is the Smart Shopper Surprize, which is a raffle program that is held every six months. However, the problems faced today, namely in the dissemination of information and promotion around the event, are still lacking. there is a decrease of about 15% from the target figure of 400 new member registrations per month. With the development of this promotional video, it is hoped that it can increase the number of loyal customers and provide the latest information to customers about the ongoing Smart Shopper Surprize program. The methods used are: Data Collection, SWOT Analysis, Media Design Analysis and Media Production Concept (KPM). The results obtained from this study are a promotional video for the Smart Shopper Surprize event which can be used to increase the number of new member registrations and increase visitor traffic each month.